The girl I left behind - Endō, Shūsaku 1923-1996 (New Directions, 1995)
A man who caused a girl to fall in love with him by playing up his deformity, then seduced and abandoned her, is haunted by her memory. A study of the workings of conscience. By a Japanese Catholic writer, author of Silence.
Aus dem Japan. übers.
Keywords: Japan -- Fiction; Fiktionale Darstellung; Bildungsromans